Evaluation of Waste Transportation Routes in Salatiga City - Haritsa, Rifda Tsaqifarani; Maryono, Maryono; Rahadian, Rully; Hermawan, Ferry; Warsito, Budi (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
The problem of waste transportation is a major challenge in waste management in Salatiga City. With the amount of daily waste generated reaching 457.81 m³ and the volume transported only around 327.33 m³, the level of waste transportation has only reached 71.72%. This study aims to evaluate and optimize the current waste transportation route through a spatial approach using QGIS software. The methods used include field observation, primary and secondary data collection, and spatial analysis of the distribution of routes and workloads of the transport fleet consisting of 9 arm roll units and 1 dump truck unit, with a total average daily trip of 58 trips. The results of the comparison between the existing route and the planned route show a daily route length efficiency of 10.57 km (1.15%), fuel consumption savings of 2.73 liters per day, and travel time efficiency of 25 minutes. The volume of transported waste also increased from 83,730 kg/day to 89,500 kg/day (up 6.89%), which was achieved through more optimal route planning, additional trips to TPS Boja and Tingkir, and equalizing the workload between drivers. The results of this study confirm that GIS-based route optimization can increase the efficiency of distance, fuel, time, and productivity of the waste transportation system as a whole in Salatiga City.